PENGARUH HADIS PUASA SUNNAH TERHADAP MOTIVASI MENUNTUT ILMU PADA KOMUNITAS KAJIAN FIQIH MUSLIMAH - Murtini, Nurul Budi; Nursyifa Syafiah; Taqnain (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
Sunnah fasting can also be called tathawwu fasting. Tathawwu means getting closer to Allah by doing non-obligatory acts of worship. Motivation is something that encourages or moves both from within and from outside an individual. Motivation is divided into two, namely intrinsic motivation and extrinsic motivation. This research aims to examine the influence of the Sunnah fasting hadith on motivation to seek knowledge in the Muslimah Fiqh Study community. The approach used in this research is a quantitative approach. The population of this research is the Muslimah Fiqh Study community which focuses on studying fiqh of Muslimah online. Among what the community learned was the hadith of sunnah fasting and the participants tried to practice it. The total sample was 30 people taken using simple random sampling technique. The instrument used was a questionnaire with a Likert scale. The data analysis technique used simple linear regression with the help of statistical calculation applications. The results of this research show that the hadith of sunnah fasting has a significant effect on motivation to seek knowledge in the Muslimah Fiqh Study community. The magnitude of the influence of the Sunnah fasting hadith on motivation to seek knowledge in the Muslimah Fiqh Study community is 32%.